La Plaine Saint-Denis no movimento de reestruturação da região parisiense - Rafael Faleiros de Padua (Confins)
Today, the transformation process of old industrial areas has been placed on the agendas of regional communities. Faced with a social crisis provoked by the deindustrialization of large industrial regions, state organizations have been pursuing ways to revive these areas, revealing a process encompassing various strategies which manifest as land politics, involving areas on a broadened scale, transforming their very essence. This paper aims to investigate this process in the Plaine Saint-Denis region where, through strategic planning coordinated by the local community, the objective is to restore economic vigour to places in the Paris metropolitan area. However, this process is achieved by producing new social contradictions, increasing segregations experienced by impoverished segments of society.